Achieving Integration of Nigerian Cadastral and Topographic Information Systems Based on the German AAA Model (Global Journal of Science Frontier Research, 2016)
Now more than ever before data integration has become a very important issue because of the problems associated with heterogeneous geospatial data. It is almost impossible to handle heterogeneous data in a coherent manner because different data sets have different methods of acquisition, different representations, different resolutions and quality, and are based on different data models. Analysis of different data sets becomes difficult and data sharing almost impossible. Germany successfully integrated their topographic, cadastral, and geodetic data sets into a single application schema called the AAA data model. This ensured standardization and the elimination of redundancies leading to coherent analyses and data sharing. In Nigeria, the national mapping agency is the custodian of topographic and geodetic data sets while cadastral data sets are the responsibilities of the various state governments as stipulated in the Nigeria Land Use Act.
Keywords: geospatial data sets; cadastral and topographic data; integration; german AAA data model